Addition of Alcohols onto Electron-Deficient Heteroarenium Salts: A Reversible Covalent Bonding Process under Basic Conditions - Chen, Baoli; Li, En; Song, Feifei; Guimond, Nicolas; Chen, Jiean; Huang, Yong (Synlett, 2023)
The reversible addition of benzyl alcohol onto heteroarenium salts under basic conditions was studied. Fine-tuning of the nature of the arenium and substituents allowed the discovery of a range of pyrimidinium substrates that can undergo C6-selective alcohol addition. Crossover experiments were also performed to confirm the addition-elimination equilibrium under basic conditions.
Keywords: heteroarenium salts; alcohols; reversible addition; basic conditions